2016
DOI: 10.1007/s00213-016-4212-2
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of the psychostimulant effects of caffeine: implications for substance use disorders

Abstract: Background The psychostimulant properties of caffeine are reviewed and compared with those of prototypical psychostimulants, able to cause substance use disorders (SUD). Caffeine produces psychomotor activating, reinforcing and arousing effects, which depend on its ability to disinhibit the brake that endogenous adenosine imposes on the ascending dopamine and arousal systems. Objectives A model that considers the striatal adenosine A2A-dopamine D2 receptor heteromer as a key modulator of dopamine-dependent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
114
1
17

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(159 citation statements)
references
References 204 publications
1
114
1
17
Order By: Relevance
“…It is more likely that caffeine, by its antagonism of A2AR in striatal pathways, would facilitate the adenylate cyclase inhibition induced by DA D2 activation (Ferré 2008). More recently, the same author highlighted the role of the striatal A2A-D2 receptor heteromer as the main target of caffeine and by which caffeine potentiates the acute and long-term effects of prototypical psychostimulants (Ferré 2016).…”
Section: Discussionmentioning
confidence: 97%
“…It is more likely that caffeine, by its antagonism of A2AR in striatal pathways, would facilitate the adenylate cyclase inhibition induced by DA D2 activation (Ferré 2008). More recently, the same author highlighted the role of the striatal A2A-D2 receptor heteromer as the main target of caffeine and by which caffeine potentiates the acute and long-term effects of prototypical psychostimulants (Ferré 2016).…”
Section: Discussionmentioning
confidence: 97%
“…Earlier research showed an association between caffeine administration and dose-dependent increases in self-administration of stimulants (Schenk et al, 1996). The effect of caffeine on dopamine receptors has been suggested as a mechanism underlying its potentiation of other psychostimulants (Cauli and Morelli, 2005; Ferré, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Third, neurobiological evidence supports the possibility that frequent ED consumption might contribute to an increased risk for SUD due to caffeine’s ability to potentiate the addictive properties of other substances (Ferré, 2016). Laboratory studies have shown that caffeine enhances nicotine’s reinforcing and analgesic effects and potentiates the addictive properties of other stimulant drugs (Jones and Griffiths, 2003; O’Neill et al, 2015; Sigmon and Griffiths, 2011; Tanda and Goldberg, 2000).…”
Section: Introductionmentioning
confidence: 95%
“…Caffeine is the most commonly used psychostimulant worldwide and mainly consumed in forms of coffee, tea, energy drink, and soda [1][2][3][4] . Although caffeine is mostly considered to be non-addictive, the observed physical and psychological dependence 5,6 consolidate its regular consumption [7][8][9] through the caffeineinduced reinforcing effects 10 , as well as the motive to resist withdrawal symptoms 11 and to increase alertness 12 . Higher alertness after acute caffeine intake 13 mirrors a reduced homeostatic sleep pressure, which is also evident in a reduced depth of sleep 14 .…”
Section: Introductionmentioning
confidence: 99%